Usuwanie mikrozanieczyszczeń estrogenicznych w procesie fotokatalizy wspomaganym sorpcją i nanofiltracją = The removal of estrogenic micropollutants by means of photocatalysis process enhanced with sorption and nanofiltration - Dudziak, Mariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper discusses results of studies on the development of the effective method of treatment of water contaminates with estrogenic micropollutants. Photocatalysis enhanced with sorption and nanofiltration was used. The effectiveness of 17?-estradiol (natural estrogenic compound) and bisphenol A (anthropogenic estrogenic compound) removal was evaluated.
Keywords: usuwanie mikrozanieczyszczeń estrogenicznych; oczyszczanie wody; removal of estrogenic micropollutants; water treatment